Factors associated with time to presentation for individuals with symptomatic uncomplicated genital gonorrhoea: a cross sectional cohort study of GToG trial participants. (2nd January 2020) - Ayinde, Oluseyi; Tan, Wei; Hepburn, Trish; Ross, Jonathan D C
Abstract : Objectives: To determine the variation in the time from onset of symptoms to clinical presentation (time to presentation [TTP]) in a cohort of sexual health attendees with symptomatic uncomplicated genital gonorrhoea and to identify factors associated with TTP. Methods: Participants were recruited from 14 clinics across England into the 'Gentamicin for the Treatment of Gonorrhoea (GToG)' trial between October 2014 and November 2016. Multivariable analysis was performed using prospectively collected demographic, behavioural and clinical data in a subset of the GToG study cohort presenting with genital discharge and/or dysuria who tested positive for Neisseria gonorrhoeae using a nucleic acid amplification test. The results were expressed as geometric mean ratios (GMR) with 95% CI for time to presentation after onset of symptoms. Results: 316 participants (269 men and 47 women) with a median age of 27.6 years (IQR 23.0–34.8) were included. 194 (61%) were Caucasian, 29 (9%) Black African, 27 (9%) Asian and 66 (21%) of other ethnicities. Median TTP was 3 days for men (IQR 2–7) and 14 days for women (IQR 7–21). Participants reported genital discharge (297/316 [94%]), dysuria (251/316 [79%]), both genital discharge and dysuria (232/316 [73%]) and other concurrent symptoms 76/316 (24%) (e.g., rectal bleeding or genital itching). 45/316 (14%) participants reported sexual contact while symptomatic, of whom TTP was more than 7 days in 32/45 (71%). A longer TTP was associated with gender (female cf. male, GMR 2.34 [1.67 to 3.26]), no prior history of gonorrhoea (GMR 1.46 [1.15 to 1.86]), 'regular' or 'ex-regular' sexual relationship (regular cf. one off GMR 1.35 [1.05 to 1.72]); ex-regular cf. one off GMR 1.88 [1.12 to 3.14]), and being heterosexual (GMR 1.69 [1.31 to 2.19]). Conclusion: Specific demographic and behavioural factors are associated with a longer TTP in individuals with symptomatic genital gonorrhoea. Detailed knowledge of these factors can be used to prioritise and optimise gonorrhoea management and prevention.